Implementasi Program Makanan Bergizi Gratis terhadap Pengeluaran Keuangan Siswa Sekolah Menengah Atas - Mica Siar Meiriza; Shintami Oktavia; Dhing Oktavia Anggraini; Maryatul Zulmi; Raisya Chairina Arira Siregar (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the effect of the implementation of the free nutritious food policy on the financial expenditure of high school students. This study uses a quantitative method with an associative approach. The population in this study is all students at the upper secondary school level, with a sample of 163 respondents obtained through certain sampling techniques. Data collection was carried out through questionnaires, while data analysis using the help of SPSS and Microsoft Excel included validity, reliability, normality tests, linearity, simple linear regression, and determination coefficient (R2) tests. The results showed that all items were declared valid and reliable, the data was distributed normally, and the relationship between variables was linear. The results of the regression test showed that the implementation of the free nutritious food program policy had a positive and significant effect on students' financial expenditure with a significant value of 0.000 and a regression coefficient of 0.618. In addition, the determination coefficient value (R2) of 0.328 shows that the implementation variable is able to explain 32.8% of the variation in student financial expenditure. Thus, it can be concluded that the implementation of the free nutritious food program has a significant influence on the financial expenditure of high school students.